(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
India has a long history of giving legal protection to working children suffering from exploitation. There are specific provisions both in the Directive Principles of state policy and the Fundamental Rights of the Constitution of India on the rights and protection of children. This policy aims at successfully rehabilitating working children withdrawn from employment and reducing the incidence of child labor progressively through a number of measures. More children under fourteen live in India than there are in the entire United States. To feed, educate, and treat these children is India’s most pressing development concern. This paper a brief review of migratory child labor, and focus of nature of the socio-economic condition and problems.